2022
DOI: 10.1038/s41419-022-05364-w
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced apoptosis of Leydig cells is mediated by excessive mitochondrial fission and inhibition of mitophagy

Abstract: Cadmium is one of the environmental and occupational pollutants and its potential adverse effects on human health have given rise to substantial concern. Cadmium causes damage to the male reproductive system via induction of germ-cell apoptosis; however, the underlying mechanism of cadmium-induced reproductive toxicity in Leydig cells remains unclear. In this study, twenty mice were divided randomly into four groups and exposed to CdCl2 at concentrations of 0, 0.5, 1.0 and 2.0 mg/kg/day for four consecutive we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 54 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…The reduction in the T, LH, and FSH hormone levels was also found in other studies exposed to AFB 1 . , Undoubtedly, the numbers and function of LCs directly affect T production . 3β-HSD is the biomarker of the LCs lineage . From the immunohistochemical results in our study, AFB 1 reduced 3β-HSD-positive cells, indicating AFB 1 caused a decrease in the number of LCs in mice testis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The reduction in the T, LH, and FSH hormone levels was also found in other studies exposed to AFB 1 . , Undoubtedly, the numbers and function of LCs directly affect T production . 3β-HSD is the biomarker of the LCs lineage . From the immunohistochemical results in our study, AFB 1 reduced 3β-HSD-positive cells, indicating AFB 1 caused a decrease in the number of LCs in mice testis.…”
Section: Discussionsupporting
confidence: 87%
“…13 3β-HSD is the biomarker of the LCs lineage. 37 From the immunohistochemical results in our study, AFB 1 reduced 3β-HSD-positive cells, indicating AFB 1 caused a decrease in the number of LCs in mice testis. Consistently, our results also showed that AFB 1 exhibited cytotoxicity on TM3 cells, evidenced by the disrupted cellular ultrastructure and decreased cell viability and density.…”
Section: Discussionmentioning
confidence: 49%
“…The primary routes of human exposure are inhalation and ingestion, leading to the accumulation of Cd in vital organs [ 5 , 6 ], including the kidneys, lungs, and intestines [ 7 ]. Exposure to Cd can result in various types of systemic damage, including liver and kidney dysfunction, pulmonary edema, and reproductive toxicity [ 4 , 8 , 9 ]. Moreover, Cd has been identified as a carcinogen, with occupational or environmental exposure being associated with lung, breast, bladder, and other types of cancers [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher Cd exposure may result in a higher sperm mtDNAcn through increasing oxidative stress. A study based on animal experiments reported that Cd exposure may decrease Leydig cells' function by increasing oxidative stress, which leads to an increase in mtDNAcn [29]. Another study reported prostate cancer patients' blood Cd was positively associated with blood mtDNAcn [30].…”
Section: Introductionmentioning
confidence: 99%